Nomenclatural adjustments in Brazilian Cereeae (Cactaceae) - Taylor, Nigel P.; Zappi, Daniela C. (Phytotaxa, 2020)
Recent taxonomic activity has resulted in taxa belonging to Cactaceae tribe Cereeae from limestone outcrops in Eastern Brazil being upgraded as a species and genus, respectively: Melocactus pachyacanthus Buining & Brederoo  (1975: 1) subsp. viridis N.P. Taylor (1991: 40) and Pilosocereus Byles & Rowley (1957: 66) subg. Gounellea Zappi (1994: 36). However, two of the new names associated with these changes have proved to be either illegitimate or invalid under the rules of the International Code of Nomenclature for plants and fungi (Turland et al. 2018). The following notes provide legitimate or valid names for the taxa involved.